Darwin wasps of the subfamily Pimplinae (Hymenoptera: Ichneumonidae) of Mexico: genera Neotheronia Krieger, Nomosphecia Gupta and Xanthopimpla Saussure - Khalaim, Andrey I.; Ruíz-Cancino, Enrique (Zootaxa, 2021)
Mexican species of three pimpline genera, Neotheronia Krieger (24 species), Nomosphecia Gupta (two species) and Xanthopimpla Saussure (one species) are reviewed. Five species of Neotheronia are described as new to science: N. altacima sp. nov., N. bonita sp. nov., N. juanitae sp. nov., N. tequila sp. nov. and N. zaldivari sp. nov. Neotheronia septemtrionalis Krieger, 1905 is found to be a junior synonym of N. nigrolineata (Brullé, 1846) (syn. nov.). Seven species of Neotheronia are new records from Mexico: N. bostrandae Gauld, N. charli Gauld, N. donovani Gauld, N. hespenheidei Gauld, N. lizzae Gauld, N. lloydi Gauld and N. matamorosi (Brullé). Moreover, Neotheronia concolor Krieger, N. lineata (Fabricius), N. mellosa (Cresson) and N. nigrolineata (Brullé) are recorded for the first time from Honduras, and N. rosai Gauld is recorder for the first time from Guatemala. South American species Neotheronia cristata Krieger is excluded from the Mexican fauna. Identification keys to species of Neotheronia and Nomosphecia occurring in Mexico are provided.